Increasing human resource capacity in African countries: A nursing and midwifery Research Summit. (2017) - Sun, Carolyn; Ferng, Yu-hui; Gombachika, Belinda; Wakasiaka, Sabina; Misore, Juliana; Cato, Kenrick; Omoni, Grace; Klopper, Hester; Malata, Address; Dohrn, Jennifer; Larson, Elaine
Abstract: Background: As global efforts to increase the nursing and midwifery workforce intensify to improve access and quality of healthcare, clinical nursing and midwifery research must increase concomitantly to provide a solid evidence base for these clinicians. To maximize research resources in resource-poor regions, the research team collaborated with regional experts in southern and eastern African countries to convene a Research Summit in Nairobi, Kenya. Objectives were to: build a network of midwifery and nurse scientists, identify regional gaps in knowledge and priorities for their research, develop strategies that address these gaps, and initiate a mentorship plan. Purpose: To review methods leading up to organizing and convening as well as the evaluation of the aforementioned Research Summit. Methods: A two-day regional Summit was convened; appropriate experts from 12 countries participated. In a year-long collaborative process, regional experts and research priorities were identified; during the Summit, a fluid agenda incorporated findings from workgroups. Summative evaluations were completed by participants and planners. Results: Through the Summit, a network of regional research experts was established; peer mentoring was initiated; research priorities were confirmed; regional action plans to address clinical nursing and midwifery research priorities were developed; and technical task forces and a steering committee were formed. Evaluations from participants, planners and core collaborators were collected. Follow up reports have been submitted by technical working groups. Conclusions: Evaluations provided favorable feedback regarding the process leading up to as well as the content of the Research Summit. While further long-term evaluations will be needed to determine the sustainability of this initiative, the Summit format afforded the opportunity for regional experts to meet, examine research priorities, and develop strategic action and mentorship plans. This paper describes a replicable method that could be utilized in other regions using available resources to minimize costs and modest grant funding.